2005
DOI: 10.1002/ctpp.200510057
|View full text |Cite
|
Sign up to set email alerts
|

PECVD of Carbon Nanostructures in Hydrocarbon‐Based RF Plasmas

Abstract: Different aspects of the plasma-enhanced chemical vapor deposition of various carbon nanostructures in the ionized gas phase of high-density, low-temperature reactive plasmas of Ar+H2+CH4 gas mixtures are studied. The growth techniques, surface morphologies, densities and fluxes of major reactive species in the discharge, and effects of the transport of the plasma-grown nanoparticles through the near-substrate plasma sheath are examined. Possible growth precursors of the carbon nanostructures are also discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…On the other hand, when the bias increases, more ions deposit closer to the nanotip bases giving rise to wider and shorter pyramidlike structures shown in the bottom panels in Fig. 6 [22], [27], [29], [30]. Quite similar results are obtained when the plasma density is changed: At higher plasma densities, the influx of building material is larger and the NAs usually feature wider bases [29], [30], in accordance with the results of numerical experiments shown in Fig.…”
Section: Plasma-aided Synthesis Of Carbon-based Nanostructuressupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, when the bias increases, more ions deposit closer to the nanotip bases giving rise to wider and shorter pyramidlike structures shown in the bottom panels in Fig. 6 [22], [27], [29], [30]. Quite similar results are obtained when the plasma density is changed: At higher plasma densities, the influx of building material is larger and the NAs usually feature wider bases [29], [30], in accordance with the results of numerical experiments shown in Fig.…”
Section: Plasma-aided Synthesis Of Carbon-based Nanostructuressupporting
confidence: 90%
“…4 to the spatial distributions of the main working species in the 0.5-m-sized vacuum chamber of the plasma reactor (the third figure from the left in the top row in Fig. 4) used for the synthesis of the carbon-nanotip structures [21], [24], [27]. The numerical results can be used to optimize the process parameters.…”
Section: Deterministic Nanofabrication and Plasma Nanosciencementioning
confidence: 99%
“…22,45 The effects considered may be particularly important for the effective control of the temperature of plasma-exposed surfaces, which is one of the critical requirements in delicate plasma applications such as surface processing and nanostructuring. 46 This work was partially supported by the Australian Research Council and the Center for Waves and Complex Systems of the University of Sydney.…”
Section: Discussionmentioning
confidence: 98%
“…The low ICP power was found more efficient for SWCNT growth under their conditions. Ostrikov et al [22] used a low-frequency (0.46MHz) ICP-PECVD system to deposit carbon nanostructures with a mixture of Ar/H 2 /CH 4 . Their results indicated that the aligned carbon nanotip structures were predominantly grown by the molecular and radical units, whereas the plasma-grown nanoparticles were crucial components of polymorphous carbon films.…”
Section: Introductionmentioning
confidence: 99%